Endothelial mineralocorticoid receptor contributes to systolic dysfunction induced by pressure overload without modulating cardiac hypertrophy or inflammation. Issue 12 (22nd June 2017) - Salvador, Ane M.; Moss, M. Elizabeth; Aronovitz, Mark; Mueller, Kathleen B.; Blanton, Robert M.; Jaffe, Iris Z.; Alcaide, Pilar
Abstract: Heart Failure (HF) is associated with increased circulating levels of aldosterone and systemic inflammation. Mineralocorticoid receptor (MR) antagonists block aldosterone action and decrease mortality in patients with congestive HF. However, the molecular mechanisms underlying the therapeutic benefits of MR antagonists remain unclear. MR is expressed in all cell types in the heart, including the endothelial cells (EC), in which aldosterone induces the expression of intercellular adhesion molecule 1 (ICAM‐1). Recently, we reported that ICAM‐1 regulates cardiac inflammation and cardiac function in mice subjected to transverse aortic constriction (TAC). Whether MR specifically in endothelial cells (EC) contributes to the several mechanisms of pathological cardiac remodeling and cardiac dysfunction remains unclear. Basal cardiac function and LV dimensions were comparable in mice with MR selectively deleted from ECs (EC‐MR −/− ) and wild‐type littermate controls (EC‐MR +/+ ). MR was specifically deleted in heart EC, and in EC‐containing tissues, but not in leukocytes of TAC EC‐MR −/− mice. While EC‐MR −/− TAC mice showed preserved systolic function and some alterations in the expression of fetal genes, the proinflammatory cytokine TNF α and the endothelin receptors in the LV as compared to EC‐MR +/+ TAC mice, no difference was observed between both TAC groups in overall cardiac hypertrophy, ICAM‐1 LV expression and leukocyte infiltration, cardiac fibrosis or capillary rarefaction, all hallmarks of pathological cardiac remodeling. Our data indicate that EC‐MR contributes to the transition of cardiac hypertrophy to systolic dysfunction independently of other maladaptive changes induced by LV pressure overload. Abstract : We report the contribution of endothelial cell mineralocorticoid receptor (EC‐MR) to systolic function in homeostatic and left ventricular pressure overload conditions. While EC‐MR does not play a role in homeostatic systolic function, it contributes to systolic dysfucntion in response to pressure overload independently of cardiac hypertrophy, cardiac fibrosis, and cardiac recruitment of inflammatory leukocytes.